The Mueller matrix of a two-layer eccentrically bianisotropic cylinder linear array with double helical conductances of the surfaces: Clarification of the magnetic symmetry groups - Abstract - Yin, W.-Y. (2014)
Journal of Electromagnetic Waves and Applications